A epistemologia da mediação em Bruno Latour - Cardoso, Tarcísio de Sá (2015)
Interdisciplinary researches have been found problems using conceptual systems founded on philosophical dichotomies such as subject/object, mind/matter, human/non-human, which are often unable to cope with emergent properties, especially interesting for such studies. In order to contribute to a maturing of the discussion interested at the border more than in the center of the disciplines, this research will study the idea of mediation that the work of Bruno Latour has given rise in its construction of a non-dualistic theory. We believe that the notion of mediation, which appears in several parts his work, is a key concept to promote a non-dualistic thinking as it establishes a mediator ground between the poles built by modern philosophy. In this sense, the present research asks: how the concept of mediation appears in the reticular thinking of Bruno Latour and what it adds to modern thought?